Andrzej Karpowicz – twórca Pracowni Zbiorów Masońskich Biblioteki Uniwersyteckiej w Poznaniu - Kurzawa, Tomasz (Biblioteka Uniwersytecka w Poznaniu, 2011)
Artykuł omawia działalność naukową i zasługi w zakresie pracy bibliotecznej twórcy Pracowni Zbiorów Masońskich Biblioteki Uniwersyteckiej – mgra Andrzeja Karpowicza. Portret Andrzeja Karpowicza przedstawiony został na szerokim tle piśmiennictwa i źródeł do dziejów wolnomularstwa oraz sylwetek autorów zajmujących się wskazaną problematyką.

This article is a tribute to Andrzej Karpowicz, the creator of the Masonic Collection Study Room at the library and discusses his research activities and achievements in library work. The profile of Andrzej Karpowicz is set against a broad background of professional literature and source materials on the history of Freemasonry and profiles of other authors in the field.
Andrzej Karpowicz – the originator of the Masonic Collection Study Room at Poznań University Library
Keywords: Biblioteka Uniwersytecka w Poznaniu; Poznań University Library; Pracownia Zbiorów Masońskich; Masonic Collection Study Room; Andrzej Karpowicz